PROPUESTA DE MEJORAMIENTO TURISTICO PARA EL PARQUE RECREACIONAL ORILLAS DEL ZAMORA”, EN LA CIUDAD DE LOJA - López Pineda., Luis Eduardo (2015)
The Ecuador offers many options because of its wide range of environmental conditions, generating an impressive diversity of habitats and vegetation types. Have been inventoried more than 920 attractions, of these, around 520 are natural, especially the national parks, forests, rivers and lakes, mountains, etc. Within the Andean region specifically in the city of Loja find the Shores Recreation Park Zamora, which is a sign of natural potential, is located along the river Zamora (north of the city of Loja part) in the 4 ½ kilometer old road to Cuenca, with an area of 13 hectares. It provides various entertainment options to satisfy the most varied tastes as it is a zone where they can engage in recreational activities. At present it is being handled by the Autonomous Decentralized City Government in order to protect and conserve watersheds under his administration has preserved the flora and fauna. The study area has a potential to become a promising site for tourist activities, observation of flora and fauna, hiking, recreation, hiking, among others, for that reason research work is called "Proposal Tourism Improvement for The Shores Of Recreational Park Zamora "in the city of Loja, this proposal served as basic guidelines for the adequacy of the trails; as well as for the implementation of the respective signaling and infrastructure of the main areas that make up the area, contributing to tourism development Shores Zamora Park. The overall objective was to "contribute to tourism development Zamora Shores Recreational Park, through the proposal of improvement thereof, which facilitates access to visitors, who can enjoy and appreciate the different natural attractions of the intervention sites. For the development of this study, it was conducted according to the specific objectives founded and supported by methods such as: scientific method, inductive-deductive method that allowed implementing each of the activities proposed in conducting this study. The first goal: "Making a tourist diagnostic for identifying tourist areas in Zamora Shores Recreational Park" methods were used; scientific and descriptive, which allowed us to know and deepen the main areas that make up the tourist attractions that owns Shores Park Zamora. The information obtained was compiled through detailed research on each of the tabs inventories attractions granted by the Ministry of Tourism (Mintur), resulting in five attractive which were analyzed and discussed by the evaluation matrix, Hierarchy II categorized among them are: Zoo, Orchid, Plant Nursery, Kartódromo and Nature Trail. 6 Second objective: "To design a proposal for improvement in tourist areas, signage and interpretive information in each area of Zamora Shores Recreational Park", we rely on scientific and mathematical method to determine the tourism carrying capacity, which is verified the state of the trails, obtaining actual data used in the formulas of the methodology of Miguel Cifuentes, could define the designs of trails, paths, senderización, positive and negative impacts, facilities, tourist, recreational and educational activities, using GPS and Geographic Information Systems (GIS) for mapping of trails. Signaling to design was based on the methodology of MINTUR, in order to maintain the level of standardization proposed by this entity, this methodology was adapted according to the specific characteristics of a Recreational Park. The designs of the signs are realized in programs Adobe Illustrator and Adobe Photoshop, once obtained these could define the entire infrastructure budget to develop. Third objective "Socialize the results obtained with entities involved, as an alternative to progress to the Shores of Zamora Recreational Park" to this analytical method, scientific tool that facilitated the socialization the project was used to Ing. Diego Castro Head of Unit Canton Tourism Loja GAD, as a result of this activity possible tourism development strategies, including for tourism promotion of the park, in order to seize opportunities with travel agencies, publicizing these natural attractions were raised, their varied flora and fauna, adequate infrastructure that allows the enjoyment of locals and tourists. However, the environment and natural wealth, have been altered by weak awareness and knowledge of the ecological and / or environmental guarding each. Upon completion of the research stages it was obtained as a final result the proposed trails and interpretive and informative signage, facilitating access to visitors, to enjoy and appreciate the different natural attractions of sites that exist in the park, improving image and services of the same, to help disseminate and promote tourism in this place of great importance and relevance in our city. The proposed models and material infrastructure and signage to be used as well as the budget, the need to invest for its implementation which is $ US $ 19,605, signs detailing costs, infrastructure and signaling are described. With the implementation of the proposal it is to boost tourism as a sustainable strategy and sustainable development, avoiding cause negative impacts to biological components of the Park. In addition to signaling contributes to raise awareness among visitors with conservation messages and also allow it to better interact capturing their attention and optimize their knowledge. In this research we conclude that signaling is limited in most areas, preventing visitors know the attractions and services offered by the park, for which it was felt advisable to place signs, pictographs, billboards, information tables which have contained relevant interpretive and interactive, the infrastructure that has the park is suitable for the enjoyment and recreation of visitors, but the limited and insufficient awareness or communication strategy and environmental education, has caused the destruction of some spaces, projecting an image negative and progressive degradation. Finally it is recommended to GAD of Loja, strengthen cooperation strategies between public and private actors in order to implement this project to promote and improve environmental and tourism management in the region and thus generate jobs to improve the quality of life of its inhabitants.